Social support and health behaviour in women living with HIV in KwaZulu-Natal - Bernhard Gaede; Sisana Majeke; Rugira Regis Marie Modeste; Joanne Rachel Naidoo; Mokete Joseph Titus; Leana R Uys (Taylor & Francis Group, 2006)
The article explores the relationship between social support and health behaviour of rural and urban women who are living with HIV in South Africa. Our study was a descriptive survey of a group of pregnant and non-pregnant women living with HIV. The sample size was 262 women, 165 from urban area and 97 from rural area. Data were collected using 3 instruments, namely a demographic questionnaire, the health behaviour schedule and the Medical Outcomes Study (MOS) Social Support Survey. Significant findings indicate that in the urban area 71% of women had disclosed their HIV status to someone, while in the rural area 49% had done so. A total of 77% of the women indicated that they were sexually active - 21% had 2 partners and 20% indicated that they had at least one episode of a sexually transmitted disease since finding out their HIV status. A total of 16% said that they currently received counselling, which was significantly more frequent in the rural sample (27%) than the urban (11%). The membership of support groups is at 12% among the participating women, and social support as well as membership of a support group was higher in the rural group than the urban group. Good social support showed an association with condom use, support group attendance and taking vitamins. However, receiving counselling as well as membership of a support group showed stronger association with positive health behaviour than social support on its own. The higher social support was not associated with increased disclosure.